Texture Quantification in Y Ba 2 Cu 3 O 7 Superconducting Films - Gonzalez, J.C. (2020)
Y Ba2Cu3O7 epitaxial superconducting film is consequence of an optimum epitaxial growth process of superconducting grains. Also, the substrate's epitaxy has a direct repercussion on the lm microstructure and its physical properties. Conventional characterization techniques such as: scanning electronic microscopy, and x ray difrraction, allowed us to obtain a quick assessment of epitaxy quality through of texture quantification of the film. We present the results of texture quantification in Y Ba2Cu3O7 superconducting films.